EFL Teachers’ Perspectives on Teaching Writing and Presenting Skills through Project-Based Learning in the Merdeka Curriculum - Ummah, Hoirul; Priyana, Joko (JOLLT Journal of Languages and Language Teaching, 2025)
Project-based learning (PjBL) has been widely applied in English language education, yet its classroom implementation often presents considerable challenges for teachers. This qualitative study investigates these challenges in teaching writing and presenting skills within the context of the Merdeka Curriculum, where integrated skills are emphasized as key learning outcomes. Four English teachers who have actively applied PjBL participated in the study. Data were collected through semi-structured interviews and an open-ended questionnaire, which were analyzed thematically using Braun and Clarke’s framework to enhance trustworthiness. Triangulation techniques were employed during data collection and analysis. The findings revealed several challenges, with the most critical being the limited facilities and unequal access to resources, as well as the complexities of assessing group projects. These findings underscore the importance of professional development, curriculum support, and institutional policy in enabling EFL teachers to teach writing and presentation skills through PjBL effectively. Addressing these challenges can improve the sustainability of PjBL practice and foster students’ engagement and skills development in English language learning.